Access Overlays: Improving Non-Visual Access to Large Touch Screens for Blind Users - Kane, Shaun; Morris, Meredith Ringel; Perkins, Annuska Z.; Wigdor, Daniel; Ladner, Richard E.; Wobbrock, Jacob O. (ACM Symposium on User Interface Software and Technology, 2011)
Many touch screens remain inaccessible to blind users, and those approaches to providing access that do exist offer minimal support for interacting with large touch screens or spatial data. In this paper, we introduce a set of three software-based access overlays intended to improve the accessibility of large touch screen interfaces, specifically interactive tabletops. Our access overlays are called edge projection, neighborhood browsing, and touch-and-speak. In a user study, 14 blind users compared access overlays to an implementation of Apple’s VoiceOver screen reader. Our results show that two of our techniques were faster than VoiceOver, that participants correctly answered more questions about the screen’s layout using our techniques, and that participants overwhelmingly preferred our techniques. We developed several applications demonstrating the use of access overlays, including an accessible map kiosk and an accessible board game.